2015
DOI: 10.1093/ehjci/jev325
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of high-risk coronary plaques identified by computed tomographic angiography and associated prognosis: a systematic review and meta-analysis

Abstract: To clarify the potential role of coronary computed tomographic angiography (CCTA) in characterizing and prognosticating high-risk coronary plaques. A systematic review and meta-analysis were conducted to compare high-risk vs. low-risk plaques and culprit vs. non-culprit lesions in patients with acute coronary syndrome (ACS) vs. stable angina (SA). High-risk plaques were defined by at least one of the following features: non-calcified plaque (NCP), the presence of spotty calcified plaque (SCP), or increased rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 35 publications
2
62
2
1
Order By: Relevance
“…(33) studied 3,158 patients with coronary CTA and found high-risk lesions (defined by the presence of both positive remodeling and low-attenuation necrotic cores) in 294 patients who were subsequently 10 times more likely to experience ACS than patients without such plaque (16% event rate in patients with high-risk plaque compared with 1.4% event rate in those without). Similarly, a recent meta-analysis showed that the risk of future ACS was 12-fold higher (odds ratio: 12.1; 95% confidence interval [CI]: 5.2 to 28.1; p < 0.0001) in patients with high-risk lesions than in those with low-risk plaques (30). Although these data support adverse plaque detection as a means of identifying high-risk patients, confirmation in large-scale multicenter clinical trials is required.…”
Section: Adverse Plaque Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…(33) studied 3,158 patients with coronary CTA and found high-risk lesions (defined by the presence of both positive remodeling and low-attenuation necrotic cores) in 294 patients who were subsequently 10 times more likely to experience ACS than patients without such plaque (16% event rate in patients with high-risk plaque compared with 1.4% event rate in those without). Similarly, a recent meta-analysis showed that the risk of future ACS was 12-fold higher (odds ratio: 12.1; 95% confidence interval [CI]: 5.2 to 28.1; p < 0.0001) in patients with high-risk lesions than in those with low-risk plaques (30). Although these data support adverse plaque detection as a means of identifying high-risk patients, confirmation in large-scale multicenter clinical trials is required.…”
Section: Adverse Plaque Characteristicsmentioning
confidence: 95%
“…Beyond this simple categorization, coronary CTA has demonstrated its ability to identify a range of adverse plaque characteristics, including positive remodeling, necrotic core, napkin ring sign, and spotty calcification (Figure 2) (30). Positive remodeling is defined by eccentric plaque formation with relative preservation of the lumen caliber.…”
Section: Adverse Plaque Characteristicsmentioning
confidence: 99%
“…23 Also, the protrusion of the atheroma in the vessel lumen causes a shift from a normal, laminar flow, with evenly distributed transverse and shear stress, to a tur- 60 and microcalcification within the plaque (referred to as spotty calcifications). 61,62 CCTA is also able to evaluate the overall degree of calcification of the coronary tree by using the coronary artery calcium score, which has been shown to have a high predictive capacity for major adverse cardiovascular events, being combined with traditional cardiovascular risk factors (c-statistic of 0.93). luminal attenuation gradient through a coronary stenosis.…”
Section: Shear Stress and Vulnerable Plaquesmentioning
confidence: 99%
“…[8][9][10][11][12] There may be associated active vascular remodeling, a process characterized by enlargement of the vessel diameter at the site of the plaque and the presence of spotty calcifications within the plaque. 9,13 invasive and noninvasive imaging techniques for Plaque characterization CCTA is currently the most common used technology for the noninvasive assessment of coronary atherosclerotic plaques. This technique has the unique ability to identify the presence of low-attenuation atheroma or napkinring sign within the plaque, described as a ring-shaped area with a low density upon CT examination, which is surrounded by a high-density attenuation.…”
Section: Plaque Imaging -Features Of Vulnerabilitymentioning
confidence: 99%